Myocarditis complicated by massive right ventricular thrombus and extensive pulmonary embolism: A case report - Jiang, Xiao-juan; Zhang, Wei-yi (Frontiers in Surgery, 2022)
An intracardiac thrombus may develop as a consequence of myocarditis, and in rare cases, a dominantly right ventricular thrombus develops, which may impair cardiac function and even cause life-threatening cardiovascular events. We report a 24-year-old man presented with recurrent episodes of palpitation and precordial discomfort after catching a cold 2 months ago. Transthoracic echocardiography (TTE) and computed tomography pulmonary angiogram (CTPA) revealed a mass attached to the apex of the right ventricle and extensive bilateral pulmonary artery emboli. There was no indication where the thrombi originated from in this young patient without any underlying disease except myocarditis. Pulmonary endarterectomy and embolectomy of pulmonary arteries and right ventricle were performed. Postoperative pathological results confirmed the presence of fibrinous necrosis and hemosiderin deposition. The formation of an intraventricular thrombus is closely related to myocarditis, which can affect individuals of all ages, but especially young people. Thus, patients with myocarditis should be closely monitored and followed up because of the increased risk of extensive thrombosis.